CBIO-12. THE ROLES OF lncRNAs IN GBM RADIATION RESISTANCE AND TUMOR RECURRENCE. (9th November 2020) - Stackhouse, Christian; Rowland, James; Anderson, Joshua; Wang, Jelai; Nguyen, Thanh; Yue, Zongliang; Chen, Jake; Ianov, Lara; Gillespie, Yancey; Willey, Christopher
Abstract: Glioblastoma multiforme (GBM) almost invariably recurs and tumors exhibit resistance to conventional therapies. One mechanism of resistance is enhanced DNA damage response (DDR) to alkylating chemotherapy or radiation therapy (RT). We have generated 8 novel GBM patient-derived xenograft (PDX) models of tumor recurrence following serial in vivo irradiation (6 x 2Gy fractions over 2 weeks for 6+ rounds). RNA sequencing has revealed enrichment of a number of DDR pathways in the RT selected (RTS) PDX. Differential enrichment across the RTS PDX suggests multiple molecular routes to acquired RT resistance. We have also identified differential enrichment of molecular signatures for cell cycle progression, stemness, and chromatin remodeling all suggesting decreased proliferation, increased stemness, and more compacted chromatin states associated with RTS PDX. We have identified altered kinase signaling in RTS PDX that may suggest targetable signaling pathways using small molecule inhibitors. Integrated '–omics' analysis has identified SRC family kinases and altered expression of collagens related to the RTS profile. Long non-coding RNAs (lncRNA) have the potential to regulate molecular phenotypes through nucleic acid binding. We have identified 269 lncRNAs significantly differentially expressed in the RTS condition. We have determined that a number of these transcripts have DNA binding potential in gene regulatory regions proximal to kinase, DDR, cell cycle, stemness, and chromatin remodeling genes. Analysis of lncRNAs and genes proximal to their binding sites has revealed regulatory networks potentially governing cell fate and phenotype. We have observed complex correlations of some of these transcripts, such as ZFAS1, which has a positive correlation with expression of stemness-promoting genes and simultaneous inverse correlation with cell cycle genes. This suggests ZFAS1 could be a phenotypic switch between a RT-sensitive proliferating cell and a RT-resistant non-proliferating stem-like cell. LncRNAs may represent a novel therapeutic target for the treatment of therapy resistant, recurrent GBM.